What’s New in the Toolbox for Constipation and Fecal Incontinence? - Lee, Yeong Yeh (Frontiers in Medicine, 2014)
Constipation and faecal incontinence are common complaints predominantly affecting the elderly and women. They are associated with significant morbidity and high healthcare costs. The causes are often multifactorial and overlapping. With the advent of new technologies, we have a better understanding of their underlying pathophysiology which may involve disruption at any levels along the gut-brain-microbiota axis. Initial approach to management should always be the exclusion of secondary causes. Mild symptoms can be approached with conservative measures that may include dietary modifications, exercise and medications. New prokinetics (e.g. prucalopride) and secretagogues (e.g. lubiprostone and linaclotide) are effective and safe in constipation. Biofeedback is the treatment of choice for dyssynergic defecation. Refractory constipation may respond to neuromodulation therapy with colectomy as the last resort especially for slow-transit constipation of neuropathic origin. Likewise, in refractory FI, less invasive approach can be tried first before progressing to more invasive surgical approach. Injectable bulking agents, sacral nerve stimulation and SECCA procedure have modest efficacy but safe and less invasive. Surgery has equivocal efficacy but there are promising new techniques including dynamic graciloplasty, artificial bowel sphincter and magnetic anal sphincter. Despite being challenging, there are no short of alternatives in our toolbox for the management of constipation and FI.